Characterization of pre-columbian pottery of Chakipampa and Lima style - Pillaca, M. (2009)
This paper presents a comparative study of two pre-Columbian pottery styles which were associated at the Maranga Complex: Lima and Chakipampa, that initially was believed to be produced in Ayacucho. However, using physical techniques (diffraction and fluorescence X-ray) could be determined that they were produced with local raw materials specific to the Rimac valley, showing significant differences with the results of Chakipampa style pottery fragments recovered from the site Conchopata, Ayacucho.